2020
DOI: 10.1155/2020/3196427
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moxibustion on the Intestinal Flora of Rats with Knee Osteoarthritis Induced by Monosodium Iodoacetate

Abstract: In this study, a knee osteoarthritis (KOA) rat model induced by monosodium iodoacetate (MIA) was used to study the effect of moxibustion on improving knee cartilage damage and its effect on the intestinal flora. The experimental rats were divided into the normal group (N), model group (M), moxibustion treatment group (MS), and diclofenac sodium treatment group (DS). After 4 weeks, cartilage pathological damage in the knee joint was evaluated using hematoxylin-eosin and safranin O-fast green staining an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 49 publications
0
16
0
Order By: Relevance
“…Recent studies have demonstrated that Lactobacillus genus was decreased in OA and Lactobacillus genus supplementation improved WOMAC and visual analog scale scores (Chen et al 2021 ; Bonato et al 2022 ; Lei et al 2017 ). Oral administration of Lactobacillus species was effective in alleviating OA symptoms, cartilage destruction, proinflammatory cytokines and macrophage infiltration in a couple of studies (Lei et al 2017 ; So et al 2011 ; Coulson et al 2013 ; Collins et al 2015 ; Chen et al 2020 ), but the specific therapeutic mechanisms remain to be further investigated. IPA, the major metabolite of Lactobacillus, has anti-inflammatory effects in multiple disease models.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have demonstrated that Lactobacillus genus was decreased in OA and Lactobacillus genus supplementation improved WOMAC and visual analog scale scores (Chen et al 2021 ; Bonato et al 2022 ; Lei et al 2017 ). Oral administration of Lactobacillus species was effective in alleviating OA symptoms, cartilage destruction, proinflammatory cytokines and macrophage infiltration in a couple of studies (Lei et al 2017 ; So et al 2011 ; Coulson et al 2013 ; Collins et al 2015 ; Chen et al 2020 ), but the specific therapeutic mechanisms remain to be further investigated. IPA, the major metabolite of Lactobacillus, has anti-inflammatory effects in multiple disease models.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that high-fat diets contribute to severe cartilage degeneration and decrease the diversity of the GM in mice, and that wheel running exercise relieved cartilage degeneration and increased GM diversity induced by high-fat diets ( Li et al, 2021 ). Chen et al also found that the abundance and diversity of the GM were reduced in OA, and moxibustion showed a favorable regulatory effect on the GM ( Chen et al, 2020 ). These results suggest that MY can improve intestinal health in patients with OA by increasing GM diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research has shown that it directly promotes knee cartilage repair, in the meanwhile regulates the composition of the intestinal flora to prohibit inflammatory factor release. 23 Some RCTs have suggested that moxibustion therapy is a safe choice for treatment. 9 , 24 , 25 However, the top-cited were the standard of meta-analysis, indicating that the number of RCTs in this field is relatively limited and the quality needs to be improved.…”
Section: Discussionmentioning
confidence: 99%